Determining the Feasibility of Ambulance-Based Randomised Controlled Trials in Patients with Ultra-Acute Stroke: Study Protocol for the “Rapid Intervention with GTN in Hypertensive Stroke Trial” (RIGHT, ISRCTN66434824) - Sandeep Ankolekar; Gillian Sare; Chamila Geeganage; Michael Fuller; Lynn Stokes; Nikola Sprigg; Ruth Parry; A. Niroshan Siriwardena; Philip M. W. Bath (Stroke Research and Treatment)
Background. Time from acute stroke to enrolment in clinical trials needs to be reduced to improve the chances of finding effective treatments. No completed randomised controlled trials of ambulance-based treatment for acute stroke have been reported in the UK, and the practicalities of recruiting, consenting, and treating patients are unknown. Methods. RIGHT is an ambulance based, single-blind, randomised controlled trial with blinded-outcome assessment. The trial will assess feasibility of using ambulance services to deliver ultra-acute stroke treatments; a secondary aim is to assess the effect of glyceryl trinitrate (GTN) on haemodynamic variables and functional outcomes. Initial consent, randomisation, and treatment are performed by paramedics prior to hospitalisation. Patients with ultra-acute stroke (≤4 hours of onset) are randomised to transdermal GTN (5 mg/24 hours) or gauze dressing daily for 7 days. The primary outcome is systolic blood pressure at 2 hours. Secondary outcomes include feasibility, haemodynamics, dependency, and other functional outcomes. A nested qualitative study is included. Trial Status. The trial has all relevant ethics and regulatory approvals and recruitment started on February 15, 2010. The trial stopped recruitment in December 2011 after 41 patients were recruited. Trial Registration. The trial registration number is ISRCTN66434824 and EudraCT number is 2007-004766-40.